KEPEMIMPINAN GURU DALAM PEMBELAJARAN DI ERA DIGITAL - Mita Septiana; Dian Hidayati (Manajemen Pendidikan, 2022)
Digital era requires teachers to be able to package learning activities by utilizing digital technology. The purpose of this study is to find out how teachers lead students in learning activities in the digital era and find out the impact of the digital era on learning and teachers. This research is a descriptive qualitative research with observation and interview data collection techniques. The results of this study are the development of the digital era, making students and teachers learn not limited by space and time. Teachers need to prepare learning plans related to digital materials and media that will be used. The use of digital media such as google form, google classroom, powerpoint, various learning applications, blogger, quizizz, google meet video conference, and zoom meeting have been used by teachers. Digital era has a positive and negative impact on the implementation of learning and for teachers. The positive impacts are (1) digital media makes it easier for students to access any learning materials; (2) students enjoy digital learning media more; (3) teachers participate in various trainings to improve skills; and (4) the teacher will continue to learn new things. The negative impacts caused are (1) learning materials become wider so that essential materials are not obtained; (2) less focused learning; (3) teachers are not always able to control students one by one on the use of gadgets; and (4) the spirit and abilities of senior teachers still need to be improved. The conclusion is that teachers as student leaders in learning are expected to be able to effectively package the development of the digital era to facilitate the implementation of learning.